UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN SELF CONTROL PESERTA DIDIK DI SMP NEGERI 11 KOLAKA UTARA - Hasridayanti; Rosmiati; Nurlaelah (STKIP Subang, 2025)
This study aims to: (1) Describe why the efforts of Islamic Religious Education (IRE) teachers in enhancing students' self-control at SMP Negeri 11 Kolaka Utara have not been fully successful, and (2) Identify the indicators of students' self-control at SMP Negeri 11 Kolaka Utara. The approach used in this study is a descriptive qualitative approach, and the research method employed is a case study. Data were collected through observation, in-depth interviews, and documentation. The data analysis techniques included data collection, data presentation, data reduction, and drawing conclusions. The results of the study show that: (1) The efforts of Islamic Religious Education teachers in enhancing students’ self-control at SMP Negeri 11 Kolaka Utara include delivering religious material, giving lectures, providing advice, empowering religious activities, and conducting special guidance. (2) The indicators of self-control include: the ability to control emotions, the ability to regulate behavior, the ability to manage thoughts, the ability to maintain social relationships, and the ability to manage time and responsibilities. These efforts made by the Islamic Religious Education teachers contribute to helping students control their emotions, behave positively, think rationally, build healthy social relationships, and become more responsible in managing their time. This research concludes that the role of Islamic Religious Education teachers is highly significant in shaping the character and self-control abilities of students within the school environ ment.